"We have two different agendas": the views of general practitioners, social workers and hospital staff on interprofessional coordination for patients with chronic widespread pain. Issue 2 (4th March 2021) - Schultz, Rikke; Brostrøm Kousgaard, Marius; Davidsen, Annette Sofie
ABSTRACT: Patients with chronic widespread pain (CWP) are often unfit for work and go through lengthy treatment. In Denmark, this includes contacts with the job center in their municipality, their general practitioner (GP) and one or more hospital units. Little is known about how coordination around patients with CWP functions and is perceived by professionals. Therefore, our aim is to explore how GPs, social workers from municipality job centers and hospital staff experience interprofessional coordination for patients with CWP. Interviews with 7 GPs, 12 social workers, and 10 hospital staff were analyzed using interpretative phenomenological analysis. The participants experienced challenges with coordination, primarily in the relations between social workers and GPs. There was an over-reliance on written communication in situations where the actors had divergent agendas, opposing professional roles and conflicting approaches to time. GPs tended to lengthen the time spans for treating patients, while social workers tried to shorten them so that patients could get back to work. Applying the theory of relational coordination (RC), the findings correspond to a low level of RC, indicating a need for shared accountability, and strengthened interpersonal communication between professionals. Abbreviations : CWP: Chronic widespread pain; GPs: General practitioners; RC: Relational coordination; IPA: Interpretative phenomenological analysis.